Cortical connectivity Brain stimulation for assessing and modulating cortical connectivity and function - Rothwell, John C.; Chen, Robert (Imprint: Springer, 2012)
The study and modulation of cortical connections is a rapidly growing area in neuroscience.  This unique book by prominent researchers in the field covers recent advances in this area.  The first section of the book describes studies of cortical connections, modulation of cortical connectivity and changes in cortical connections with activities such as motor learning and grasping in primates.   The second section covers the use of non-invasive brain stimulation to study and modulate cortical connectivity in humans.  The last section describes changes in brain connectivity in neurological and psychiatric diseases, and potential new treatments that manipulate brain connectivity.  This book provides an up-to-date view of the study of cortical connectivity, and covers its role in both fundamental neuroscience and potential clinical applications.